Tolerance and Pluralism Between Religious People in the Film Kos-Kosan - Arya Andryan Dimas Prasetya; Vani Dias Adiprabowo (UNIVERSITAS PAKUAN, 2024)
This study examines the values of tolerance between religious communities as reflected in the short film